Correlation Between Clinical Indicators and Liver Pathology in Children with Chronic Hepatitis B - Chenyang Huang; Ying Lu; Ziwei Wang; Qiyu Jiang; Yi Dong; Lili Cao; Jianguo Yan; Zhiqiang Xu; Fuchuan Wang; Yinjie Gao; Junliang Fu; Min Zhang; et al. (Biomedicines)
Background: Chronic hepatitis B (CHB) in children presents a significant global health challenge, with liver inflammation and fibrosis being critical concerns for disease progression and long-term outcomes. Methods: This retrospective study analyzed 1629 pediatric CHB patients from the Fifth Medical Center of Chinese PLA General Hospital, spanning from January 2000 to December 2021. Liver biopsies were performed to assess the severity of liver inflammation and fibrosis, which were graded using the Scheuer scoring system. Key clinical indicators, including age, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyl transferase (GGT), were evaluated for their predictive value in determining disease severity using restricted cubic spline regression models. Results: Significant nonlinear associations were found between the clinical indicators and liver pathology. Older age was strongly associated with increased risks of moderate to severe inflammation (OR 2.21, 95% CI: 1.34–3.63, p = 0.002) and significant fibrosis (OR 2.22, 95% CI: 1.31–3.77, p = 0.003). Elevated ALT levels (≥80 U/L) were correlated with a higher likelihood of moderate to severe inflammation (OR 1.82, 95% CI: 1.05–3.15, p = 0.033), while higher GGT levels (≥50 U/L) were significantly associated with advanced fibrosis (OR 2.62, 95% CI: 1.72–3.99, p < 0.001). Conclusions: Regular monitoring of clinical indicators such as ALT, AST, and GGT levels plays a critical role in identifying pediatric CHB patients at higher risk of moderate to severe inflammation and significant fibrosis. Our findings highlight the value of integrating age and key biochemical markers into non-invasive diagnostic algorithms for the early detection and management of liver pathology in children.